Media Gambar Untuk Meningkatkan Proses Dan Hasil Belajar Siswa Pada Pembelajaran Pkn - Yul Eferi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2017)
Learning of civics subject at 3rd grade of SDN 18 Batang Anai Kabupaten Padang Pariaman did not optimize the media. It caused the learning process and achievement of students being low. This study is a classroom action research with two cycles aimed to improve students’ learning process and achievement by implementing media of picture. Data were collected through observastion and test. Indicators of learning proces improvement: in cycle I, score of students’ creativity is 40%, students’ motivation is 32%, students’ participation in answering question is 35%; in cycle II, score of students’ creativity is 86%, students’ motivation is 92%, and atudents’ participation in answering question is 89%. Mean of students’ test score in cycle I is 6.4 and in cycle II is 8.0. Hence, media of picture can improve students’ learning process and achievement in civics subjects.